Water-based graphene oxide inks for inkjet-printed flexible moisture energy generators - Katerina Anagnostou; Massimo Urban; Evangelos Sotiropoulos; Christos Polyzoidis; Katerina Kavalieraki; Kyriakos Mouratis; Giulio Rosati; Arben Merkoçi; Konstantinos Rogdakis; Emmanuel Kymakis (Scientific Reports)
Abstract With the need for clean sustainable energy and low-waste practices rising, battery-free technologies that run on renewable ambient energy sources are an attractive solution to these environmental concerns. Herein, Graphene oxide (GO) and GO-PEDOT: PSS water-based inks were formulated from inexpensive precursor materials following user-friendly, up-scalable methods. GO-based moisture-active films were deposited on flexible lightweight substrates using inkjet printing to fabricate Moisture Energy Generators (MEG), devices that convert ambient moisture energy variation into a voltage output. The performance of the fabricated MEGs was evaluated using a custom-made automated humidity chamber, yielding an average voltage output of Vo=183 (± 1.76) mV for pure GO and Vo=194 (± 0.97) mV for GO-PEDOT: PSS, in the relative humidity range of 45–95%. We support that this study may provide fertile ground for the development of low-cost energy harvesters for self-powered portable and wearable technologies, minimising the need for batteries and reducing electronic waste.